Serum Total Protein and Albumin Levels in Different Grades of Protein Energy Malnutrition - Chowdhury, Md Serajul Islam; Akhter, Nayeema; Haque, Mahmudul; Aziz, Rehana; Nahar, Nazibun (Journal of Bangladesh Society of Physiologist, 2009)
The present study has been designed to estimate serum total protein and albumin levels in different grades of protein energy malnutrition and this will be helpful in early diagnosis, management and rehabilitation of PEM. The serum total protein and albumin levels were studied on 20 healthy children and 30 children suffering from protein energy malnutrition of different grades. Serum total protein and albumin levels of different grades of protein energy malnutrition were significantly lowered than that of control. Lowering being maximum in grade III PEM. This lowering of total protein and albumin occur in any form of PEM and related to severity of the disease. doi: 10.3329/jbsp.v3i0.1799 J Bangladesh Soc Physiol.2008 Dec;(3):58-60.